Evaluation of medicinal herbs as a potential therapeutic option against SARS‐CoV‐2 targeting its main protease. (4th August 2020) - Upadhyay, Saurabh; Tripathi, Praveen K.; Singh, Manju; Raghavendhar, Siva; Bhardwaj, Mohit; Patel, Ashok K.
Abstract : The COVID‐19 disease caused by the SARS‐CoV‐2 has emerged as a worldwide pandemic and caused huge damage to the lives and economy of more than hundred countries. As on May 10, 2020, more than 4, 153, 300 people stand infected from the virus due to an unprecedented rate of transmission and 282, 700 have lost their lives because of the disease. In this context, medicinal plants may provide a way to treat the disease by targeting specific essential proteins of the virus. We screened about 51 medicinal plants and found that Tea ( Camellia sinensis) and Haritaki ( Terminalia chebula ) has potential against SARS‐COV‐2 3CL pro, with an IC50 for Green Tea as 8.9 ± 0.5 μg/ml and Haritaki 8.8 ± 0.5 μg/ml. The in‐silico studies suggested that Tea component Thearubigins binds to the cysteine 145 of protease active site and could be a pharmacoactive molecule. We predict that the inhibition in protease activity may be able to halt the SARS‐CoV‐2 replication cycle and therefore, we propose Green Tea, Black Tea, and Haritaki plant extracts as potential therapeutic candidates for SARS‐CoV‐2 infection. Further investigation on role of bioactive constituents of extracts is needed to establish the molecular basis of inhibition and towards expedited drug discovery.